Assessment of services rendered at village health and nutrition day in rural area of Kathua district, Jammu and Kashmir: cross-sectional study - Sangra, Sonika; Choudhary, Neha (International Journal Of Community Medicine And Public Health, 2020)
Background: Village health and nutrition days (VHNDs) are based on the principal of integration of services like nutrition, sanitation, health provision using a holistic approach. Days are organized once per week in each Anganwadi centre. These services are provided free of cost to rural people. The objective of the study was to assess services rendered at VHND in rural area of Kathua district, Jammu and Kashmir, India. Methods: The present study was descriptive cross-sectional in type, conducted in zone Budhi which is a field practice area of Department of Community Medicine, GMC Kathua. The zone Budhi consists of one primary health centre along with its six subcentres. One auxiliary nurse midwife (ANM) covered one VHND once a week. For a month, one ANM covered four VHNDs. So, out of 10 ANMs in Zone Budhi, 7 attended VHNDs with a maximum of 28 village health and nutrition days covered in a month. Results: All the ANMs made a micro-plan ahead of their visits and prepared a list of beneficiaries. Medical officers were available in 18 out of 28 sessions. ANM, anganwadi workers were available in majority of the sessions. Blood pressure apparatus and stethoscope were available in 60.71% and 67.85% sessions. In majority of sessions, the available items were weighing scales, vaccines with syringes, tablet Iron and folic acid. Services provided at the VHNDs were patients attended, pregnant women registered etc. Conclusions: Study revealed that performance of most of the sessions of VHNDs were satisfactory. So, efforts need to be initiated to fill all these gaps. And priority should be given to provide basic primary health care services to the beneficiaries.